2018
DOI: 10.25077/njk.13.1.15-33.2017
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Karakteristik Individual Perawat terhadap Kenyamanan dan Kepuasan Pasien dalam interaksi pelayanan Keperawatan

Abstract: Comfort and satisfaction in service are the reasons why patients choose the same hospital when they need treatment or come home for physical discomfort, psycho-spiritual, environmental and socio-cultural. Patient satisfaction in some areas is low with average patient satisfaction about 64,3% while according to Kemenkes (2012) patient satisfaction standard to treatment is more than 90%. This study aims to describe and analyze the comfort and satisfaction of patients in the process of interaction nursing service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
0
0
4
Order By: Relevance
“…The results showed that of the 45 respondents, most were female with 42 nurses (93.3%), while male with 3 nurses (6.7%). The results of the study are in accordance with Agritubella et al, (2017) in their conclusion showing that 82.9% of the majority of nurses in the hospital are women. This is in line with Aisyah's research, (2019) where there were 4 male respondents (14.3%) and 24 female respondents (85.7%).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that of the 45 respondents, most were female with 42 nurses (93.3%), while male with 3 nurses (6.7%). The results of the study are in accordance with Agritubella et al, (2017) in their conclusion showing that 82.9% of the majority of nurses in the hospital are women. This is in line with Aisyah's research, (2019) where there were 4 male respondents (14.3%) and 24 female respondents (85.7%).…”
Section: Resultssupporting
confidence: 88%
“…The results showed that of the 45 respondents, the majority of nurses in the inpatient ward had D3 Nursing education, there were 23 respondents (51.1%) and 22 respondents (48.9%) had a Bachelor's degree in Nursing education. The results of the study are in accordance with Agritubella et al, (2017) in their conclusion showing that half of the nurse's education of 56.1% is D3 Nursing. This is in line with Deciliawati's research, (2019) which found 21 respondents (80.8%) had a Diploma in Nursing education and 5 respondents (19.2%) had a professional education.…”
Section: Resultssupporting
confidence: 87%
“…Tabel 1 menunjukkan bahwa sebagian besar responden adalah perempuan baik untuk mentor dan mentee. Hasil penelitian ini sejalan dengan penelitian terdahulu yang menyatakan bahwa sebagian besar perawat berjenis kelamin perempuan (8). Persepsi masyarakat mengenai pekerjaan perawat identik dengan perempuan, perawat adalah pekerjaan sosial yang sejalan dengan sifat perempuan seperti sabar, memiliki kemampuan berkomunikasi,memiliki kasih sayang, berkomitmen tinggi dalam pekerjaan sehingga profesi perawat cocok untuk perempuan (8).…”
Section: Pembahasanunclassified
“…Kenyamanan dalam bekerja adalah aspek penting bagi individu bekerja karena akan memberikan pengaruh kepada daya konsentrasi, kecepatan berpikir, serta semangat individu dalam menyelesaikan pekerjaannya. Sehingga, sangat penting bagi individu untuk membangun dan menciptakan rasa nyaman bagi dirinya guna mendapatkan hasil yang produktif dan sesuai dengan apa yang diharapkan (Agritubella et al, 2018).…”
Section: Jseh (Jurnal Sosial Ekonomi Dan Humaniora)unclassified